Effective nitrogen removal of wastewater from vitamin B2 production by a potential anammox process. (October 2020) - Mai, Wenning; Hu, Tengwen; Li, Chenjing; Wu, Ruijie; Chen, Jiamin; Shao, Yanjiang; Liang, Jiawei; Wei, Yongjun
Abstract: The wastewater of vitamin B2 (VB2) production treated after anaerobic digesters contains high total nitrogen (TN) and low organic carbon. To efficiently remove nitrogen pollution in the wastewater, one lab-scale anaerobic ammonium oxidation (anammox) bioreactor was designed. Synthetic wastewater and proper conditions were used to startup the anammox process in the bioreactor. The stoichiometric parameters of the bioreactor showed that anammox process was successfully established during operation. Evaluation of the bioreactor with real VB2 wastewater suggested that the bioreactor can efficiently remove nitrogen pollution at low organic carbon situation. The optimal state of total nitrogen loading rate (TNLR) and the highest total nitrogen removal efficiency (TNRE) of the bioreactor were 0.35 kg/(m 3 ·d) and 75%, respectively. The microbiota run at day 112 (named VBM112) was significantly different with the microbiotas of the two inoculation cultures. At the phylum level, the most abundant phylum was Proteobacteria in the inoculation culture, while Bacteroidetes was the most abundant phylum in VBM112. At the genus level, the composition of nitrogen removal related microbes significantly increased in VBM112. Especially, the anammox bacteria Candidatus Kuenenia increased from 0% of the inoculation culture to 2.2% of VBM112. The analyses of running parameters and microbiota profiles confirmed the well establishment of one lab-scale anammox bioreactor, which might be helpful for future full-scale VB2 wastewater treatment startup.